Revitalizing Vital Signs: The Role of Delta Shock Index. (September 2016) - Joseph, Bellal; Haider, Ansab; Ibraheem, Kareem; Kulvatunyou, Narong; Tang, Andrew; Azim, Asad; O'Keeffe, Terence; Gries, Lynn; Vercruysse, Gary; Rhee, Peter
ABSTRACT: Introduction: Although variability in vital parameters has been shown to predict outcomes, the role of change in shock index (delta SI) as a predictive tool remains unknown. Methods: The National Trauma Data Bank (2011–2012) was abstracted for all patients aged 18 to 85 years and Injury Severity Score more than 15 with complete data. Transferred patients and patients dead on arrival were excluded. Patient demographics and injury parameters were recorded, and SI in the field, SI in the emergency department (ED), and change in SI (delta SI = ED SI−field SI) were calculated. Our outcome measure was mortality. Cox regression and Kaplan-Meier analysis was performed. Results: A total of 95, 088 patients were included, and the overall mortality rate was 11.9%. Patients with a positive delta SI had a mortality rate of 13.3% compared with 9.6% mortality rate in patients who had an unchanged or negative delta SI. After controlling for confounders, a delta SI more than 0.1 was found to be associated with an increased hazard of death (hazard ratio [95% CI] = 1.36 [1.29–1.45]) and mortality (16.6% vs. 9.5%, P < 0.001). Even in hemodynamically stable patients, a delta SI more than 0.1 was associated with increased hazard of death (hazard ratio [95% CI] = 1.29 [1.20–1.39]). Conclusions: Delta SI from field to hospital independently predicts higher mortality. It predicts higher mortality even in apparently hemodynamically stable patients with normal traditional vital signs and normal SI. Delta SI may serve as an adjunct to existing traditional vital signs for the identification of occult hypovolemic shock and higher risk of death in trauma patients.